2003
DOI: 10.1021/jp022531a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ion Size and Valence on Ion Distribution in Mixed Counterion Systems of a Rodlike Polyelectrolyte Solution. 2. Mixed-Valence Counterion Systems

Abstract: The characteristics of the ion distributions are investigated in the systems of salt-free polyelectrolyte solution with mixed-valence counterions using a cylindrical cell model. The mixtures of two species of the counterion having different valences are simulated systematically by means of the Monte Carlo method in a primitive model of the rodlike polyelectrolyte solution. The comparisons of the free fractions and the selectivity coefficients by this method are performed with the numerical solutions of the Poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…Although the limitations of NLPB in the treatment of ion sizes and correlations have been extensively discussed 15,17,18,34,39,52 , the actual extent of these limitations was not known and has been quantitatively revealed for the first time in this work. The observed deviations are larger for divalent than monovalent cations (Figs.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although the limitations of NLPB in the treatment of ion sizes and correlations have been extensively discussed 15,17,18,34,39,52 , the actual extent of these limitations was not known and has been quantitatively revealed for the first time in this work. The observed deviations are larger for divalent than monovalent cations (Figs.…”
Section: Discussionmentioning
confidence: 90%
“…Intensive theoretical work has suggested that the accuracy of NLPB in predicting ion association is limited by the inability of this theory to account for ion correlation, in addition to the limitations in treating ion size effects discussed above 16,17 . However, there is no straightforward and quantitative experimental benchmark for comparison.…”
Section: Competitive Association Of Cations: Assessing the Effects Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential in the inner zone (at distance ba) follows lineally as in a homogeneous solid state body; that allows to consider the polyelectrolyte chain as a coaxial cylindrical condenser. The presence of two kinds of counterions with different radius and valence can be considered by introducing an additional cylinder in the inner zone [18,19]. The potential 1 of the cylinder with radius b is determined by the total chain's charge including the adsorbed ions.…”
Section: Cylinder Cell Modelmentioning
confidence: 99%